2021
DOI: 10.3390/cancers13194917
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125b-5p Is Involved in Sorafenib Resistance through Ataxin-1-Mediated Epithelial-Mesenchymal Transition in Hepatocellular Carcinoma

Abstract: The mechanism of resistance to sorafenib in hepatocellular carcinoma (HCC) remains unclear. We analyzed miRNA expression profiles in sorafenib-resistant HCC cell lines (PLC/PRF5-R1/R2) and parental cell lines (PLC/PRF5) to identify the miRNAs responsible for resistance. Drug sensitivity, migration/invasion capabilities, and epithelial-mesenchymal transition (EMT) properties were analyzed by biochemical methods. The clinical relevance of the target genes to survival in HCC patients were assessed using a public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Mechanistically, miR-125b-5p promoted the EMT process and conferred stemness characteristics in PLC/PRF5-R1/R2 cells by targeting ATXN1, leading to the reduction of sorafenib sensitivity in HCC. Consistent with this, ATXN1 knockdown in HCC cells exhibited a higher CSC population and an EMT phenotype ( 174 ). Chaudhary et al.…”
Section: Mechanisms Of Ncrnas In Mediating Cancer Drug Resistancesupporting
confidence: 66%
“…Mechanistically, miR-125b-5p promoted the EMT process and conferred stemness characteristics in PLC/PRF5-R1/R2 cells by targeting ATXN1, leading to the reduction of sorafenib sensitivity in HCC. Consistent with this, ATXN1 knockdown in HCC cells exhibited a higher CSC population and an EMT phenotype ( 174 ). Chaudhary et al.…”
Section: Mechanisms Of Ncrnas In Mediating Cancer Drug Resistancesupporting
confidence: 66%
“…Studies have shown that ER stress plays a crucial role in activation of hepatic stellate cells [ 114 , 115 ] and that blocking the IRE1α–XBP1 pathway can significantly reduce liver fibrosis and tumor burden in several animal models for cirrhosis [ 47 ] and HCC [ 22 ]. Jia et al sought to provide a deeper investigation regarding the involvement of CAFs in epithelial–mesenchymal transition (EMT) in HCC [ 116 ], a process that is known to contribute to drug resistance in HCC and many other solid tumors [ 117 , 118 ]. Proteomic analyses identified that transglutaminase 2 (TG2) is substantially overexpressed in HCC cells that have obtained an EMT phenotype.…”
Section: Role Of the Tumor Microenvironmentmentioning
confidence: 99%
“…In HCC, stemness properties are closely associated with drug resistance, tumor metastasis, and recurrence [39]. Stemness properties are closely associated with the EMT phenotype, which was previously reported to contribute to sorafenib resistance in HCC [40,41]. Several other studies also reported that stemness properties are closely associated with sorafenib resistance in HCC [42].…”
Section: Discussionmentioning
confidence: 92%